Navigating diagnostic uncertainty in fahr's disease: a case report with neuroimaging correlations - Devyansh Nimodia, MBBS; Pratapsingh Hanuman Parihar, MD Radiodiagnosis; Sakshi Dudhe, MBBS; Ravishankar Patil, MD Radiodiagnosis; Paritosh N. Bhangale, MBBS; Rishitha Kotla, MBBS (Radiology Case Reports)
Fahr's disease is a rare neurological disorder which is characterized by the presence of abnormal, symmetrical, and bilateral calcifications within the basal ganglia and other cerebral areas. Seizures are 1 of the symptoms that may aid in its diagnosis. Fahr's disease is diagnosed in adults mostly. In this account, we describe the case of a male in his late 20s who was diagnosed with Fahr's disease. The patient experienced multiple seizures and severe headaches for the past 5 months. His medical history was not significant. Upon his admission to the emergency department, imaging studies (Computed Tomography and Magnetic Resonance Imaging) revealed the presence of bilateral and symmetrical calcifications situated within the bilateral corona radiata, bilateral centrum semiovale, bilateral gangliocapsular region, bilateral thalamus and bilateral dentate nucleus. Laboratory investigations ruled out alternative causes for secondary intracranial calcification. Moreover, the patient had no significant familial history. Considering the clinical, biological, and radiological evaluations, the diagnosis was concluded to align with a sporadic form of Fahr's disease.Although seizures are less common symptoms associated with Fahr's disease, the identification of bilateral and symmetrical calcifications in the basal ganglia and other regions on radiological imaging in a patient presenting with seizures should warrant consideration of this neurologic disorder, following the exclusion of other potential causes of intracranial calcification.